2019
DOI: 10.1016/j.bbmt.2018.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aging and Predonation Comorbidities on the Related Peripheral Blood Stem Cell Donor Experience: Report from the Related Donor Safety Study

Abstract: A B S T R A C TThe development of reduced-intensity approaches for allogeneic hematopoietic cell transplantation has resulted in growing numbers of older related donors (RDs) of peripheral blood stem cells (PBSCs). The effects of age on donation efficacy, toxicity, and long-term recovery in RDs are poorly understood. To address this we analyzed hematologic variables, pain, donation-related symptoms, and recovery in 1211 PBSC RDs aged 18 to 79 enrolled in the Related Donor Safety Study. RDs aged > 60 had a lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…G-primed BM numbers were also low (n = 8), with 2 donors reporting grade 2-4 pain and 3 donors reporting grade 2-4 toxicities postdonation (data not shown). Of note, among PBSC donors age 18 to 25 years in the RDSafe study, 48% experienced grade 2-4 pain and 18% had MTC toxicity [18], and earlier studies have shown increasing side effects with PBSC donation with age [2,3], so our small PBSC donor population is likely not fully reflective of the experience of older children who donate PBSCs.…”
Section: Pain and Common Toxicities Associated With The Donation Procmentioning
confidence: 92%
“…G-primed BM numbers were also low (n = 8), with 2 donors reporting grade 2-4 pain and 3 donors reporting grade 2-4 toxicities postdonation (data not shown). Of note, among PBSC donors age 18 to 25 years in the RDSafe study, 48% experienced grade 2-4 pain and 18% had MTC toxicity [18], and earlier studies have shown increasing side effects with PBSC donation with age [2,3], so our small PBSC donor population is likely not fully reflective of the experience of older children who donate PBSCs.…”
Section: Pain and Common Toxicities Associated With The Donation Procmentioning
confidence: 92%
“…Donors older than 40 years of age and donors with co-morbidities are more likely to report persistent pain at 1, 3 or 12 months after the procedure, or a failure to return to a pre-donation level of wellness. 44 Equally, longer recovery times are experienced by donors who report psychosocial challenges in their health-related quality of life surveys beforehand. 45 Particularly, related donors may describe a failure to return to a baseline quality of life or protracted discomfort twelve months after the donation.…”
Section: Long-term Complicationsmentioning
confidence: 99%